LAGU “PERFECT” OLEH ED SHEERAN DAN “MARRY YOU” OLEH BRUNO MARS DALAM PERSPEKTIF ANALISIS WACANA - Evy Tri Widyahening; Imroatul Ma’fiah (RESEARCH FAIR UNISRI, 2020)
Oral and written discourse have a textual function that contains of ideas which expressed by participants. Through discourse, community members also have the opportunity to establish communication and relationships and can interact socially and cooperate. This discourse for communication also has a close relationship with one's ability to master the four language skills. Because by mastering the four language skills and knowing the function of language, a person will easily use both oral and written discourse to communicate and interact socially. Song lyrics are one example of written discourse that generally uses beautiful and figurative language. The lyrics of the song 'Perfect' sung by Ed Sheeran and 'Marry You' sung by Bruno Mars are lyrics which also use beautiful, melancholy, sentimental, and romantic language to attract young music lovers. The lyrics of the song are one example of how written discourse can be used to communicate using seductive language with musical accompaniment and can be used as a tool to form social interactions on social media such as: facebook, twitter, radio, and television. The lyrics of the song are analyzed the content of the discourse and examined from the perspective of the songwriter's intentions, goals, and thoughts; The context and inference aspects contained in both song lyrics; Grammatical and lexical aspects to see the song's cohesion and coherence. The results of discourse analysis on grammatical and lexical aspects provide a coherent and beautiful picture of the song 'Perfect' and 'Marry You'. From the grammatical aspect, it can be seen that the reference types of the first person singular (I, speaker) and second persona reference (You, speech partner) in the two lyrics are very dominant. The lexical aspect is not very often found in the song's poetic discourse but there are full repetitions in several lines (in chorus) that show the characteristics of the two lyrics of the songs. That part is the main emphasis on the meaning and intent that the songwriters wish to convey so that the listeners of the songs are able to understand their hearts.Key Words: Oral and Written Discourse, Song Lyrics, Context and Inference Aspects, Grammatical and Lexical Aspect